ANALISIS POTENSI CALON INDEPENDEN VERSUS CALON PARTAI POLITIK PADA PEMILIHAN KEPALA DAERAH KABUPATEN KONAWE KEPULAUAN TAHUN 2020 - Najib Husain; La Ode Muhammad Elwan; Ales (Journal Publicuho, 2023)
The purpose of this study was to find out the potential of independent candidates in the midst of a battle for political party support and what are the factors that influence the vote acquisition of independent candidates in the 2020 simultaneous elections in the Konawe Islands Regency. This research method uses a qualitative approach, data sources through interviews, observation and document study. Data analysis used interactive analysis according to Mile Huberman and Saldana (2014). The results of the study show that from the electability and political image of this independent candidate, this is quite good, this is of course seen from the public's response and also seen from the vote acquisition, which is 29%. independent candidates carry out campaigns directly by visiting residents' homes and also to several villages as well as indirect campaigns by using social media to campaign and create the FBW TV Channel to introduce themselves and seek support so that they become strengths and differentiators from other candidates. Factors influencing independent candidates are the existence of a measurable and rational vision and mission, support from community leaders and first-time voters, and the image and reputation of independent candidates as a differentiator from candidates promoted by political parties. A track record in the bureaucracy and a good, intelligent and honest profile are factors of influence in political contestation in the regions.